REPRESENTATION PROBLEMS OF TRANSACTIONAL COSTS IN ENTERPRISE ACCOUNTING (Economics and region, 2017)
UDC 658.012 Yurii Pohorelov, D. Sc. (Economics), assistant professor. Hanna Kozachenko, D.Sc. (Economics), professor. Anastasiia Bilousova, PhD (Economics), assistant professor. Poltava National Technical Yurii Kondratiuk University. Representation Problems of Transactional Costs in Enterprise Accounting. There is notion of “transactional costs” considered basing on the positions of epistemological contextualism. There is built in the article classification of transactional costs. There is managerial collision found about fact that not all kinds of transactional costs that are considered in cost management can be shown in accounting according to existing methodology of accounting. Taking into account regulatory framework of accounting there are three approaches suggested about accumulation of information about enterprise transactional costs. The authors analyzed advantages and limitations of suggested approaches about accounting transactional costs. Keywords: enterprise, costs management, transactional costs, classification, accounting, representation criteria, approach for information accumulation.